Pt single-atom doped face-centered cubic phase RuGa metal ene nanoflower structure, and preparation method and application thereof

CN122999952APending Publication Date: 2026-10-30ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611118973.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]针对现有技术中Ru基氢氧化反应催化剂在高阳极电位条件下易发生氧化失活、晶体结构难以调控以及催化稳定性不足的问题,本发明提供一种Pt单原子掺杂的fcc相RuGa金属烯纳米花状结构及其制备方法

Benefits of technology

[0018]相对于现有技术,本发明的有益效果:本发明采用一步溶剂热法,以Ru前驱体、Pt前驱体和Ga前驱体为原料,在溶剂热条件下实现Pt单原子和Ga的协同掺杂,实现了Ru的相结构由稳定六方密排(hcp)相向亚稳态fcc相的转变,成功制备出具有超薄二维纳米花状形貌的fcc相Ru基金属烯催化材料。其中,Pt以单原子形式均匀分散于Ru晶格中,并与Ga协同调控Ru的晶体结构和电子结构。将Pt单原子掺杂的fcc相RuGa金属烯纳米花状结构用于电催化氢氧化反应,通过Pt单原子与Ga元素的协同调控作用,实现含氧物种和氢中间体吸附平衡的优化,从而提高氢氧化反应催化活性及长期稳定性。电化学测试结果表明,PtSA-RuGa金属烯展现出卓越的碱性氢氧化反应活性,并在高电位条件下表现出良好的抗失活能力。本发明制备工艺简单、重复性好,能够实现二维Ru基金属烯晶相及电子结构的协同调控,为高性能氢燃料电池阳极催化材料的开发提供了一种新的设计策略。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999952A_ABST
    Figure CN122999952A_ABST
Patent Text Reader

Abstract

The application discloses a kind of Pt single-atom doped face-centered cubic phase RuGa (Pt SA -RuGa) metal ene nanoflower structure and preparation method thereof, and it is applied to electrocatalytic alkaline hydroxyl reaction. Ru precursor, Pt precursor and Ga precursor are used as raw materials to realize the cooperative doping of Pt single atom and Ga under solvothermal condition, realize the phase structure of Ru from stable hexagonal close-packed (hcp) phase to metastable face-centered cubic (fcc) phase transition, and successfully obtain fcc phase Ru-based metal ene catalytic material with ultrathin two-dimensional nanoflower morphology. Pt is uniformly dispersed in Ru lattice in the form of single atom, and cooperatively controls the crystal structure and electronic structure of Ru with Ga. Test results show that Pt SA -RuGa metal ene exhibits excellent alkaline hydroxyl reaction activity, and shows good anti-inactivation ability under high potential condition. The preparation process of the application is simple, and has good repeatability, which can realize the cooperative control of two-dimensional Ru-based metal ene crystal phase and electronic structure, and provides a new design strategy for the development of high-performance hydrogen fuel cell anode catalytic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of clean and sustainable energy conversion materials technology, and specifically relates to a method for preparing RuGa-based metal olefin nanoflower structures and their application in electrocatalytic hydrogenation reactions. Background Technology

[0002] With the rapid development of hydrogen energy technology, hydrogen-oxygen fuel cells are considered an important technological path to achieve green energy transformation due to their advantages such as high energy conversion efficiency, net-zero emissions, and environmental friendliness. However, the kinetics of the anodic hydrogen oxidation reaction are easily limited by factors such as excessive adsorption of hydroxyl species and difficulty in balancing hydrogen adsorption / desorption, leading to a decrease in the reaction rate. This is a key factor restricting the performance improvement of alkaline hydrogen-oxygen fuel cells.

[0003] Currently, platinum (Pt) remains the most widely used hydrogen oxidation (HOR) catalyst, but its high cost and limited resource reserves restrict its large-scale application. Ru, as a platinum group metal, possesses excellent hydrogen adsorption / dissociation capabilities and a lower cost advantage, making it a potential candidate material to replace Pt in the hydrogen oxidation reaction. However, Ru surfaces have a strong affinity for oxygen-containing species, and under high-potential operating conditions, they are prone to surface oxidation and structural reconstruction, leading to changes in electronic structure and the covering of active sites, resulting in a rapid decline in catalytic activity. Therefore, how to ensure that Ru-based catalysts maintain excellent hydrogen oxidation activity at high potentials is a critical problem that urgently needs to be solved.

[0004] Two-dimensional metalloalkenes possess characteristics such as ultrathin structure, high specific surface area, abundant exposed active sites, and tunable lattice structure, making them promising candidates for electrocatalytic energy conversion. Ru-based metalloalkenes, as important two-dimensional noble metal catalytic materials, typically exhibit a thermodynamically stable hexagonal close-packed crystal phase. However, their lattice structure and electronic state control space are limited, making it difficult to effectively suppress the oxidation process on the Ru surface under high anodic potential conditions, thus affecting the catalyst's activity and long-term stability (Angew. Chem. Int. Ed., 65, 2026, e9761633). Therefore, constructing Ru-based metalloalkenes with a metastable face-centered cubic (FCC) crystal phase and optimizing the interaction between Ru and oxygen-containing intermediates by controlling the coordination environment and local electronic structure of Ru atoms is crucial for improving the high-potential stability and hydroxide reaction performance of Ru-based catalysts. However, due to the strong metallic bonding energy of Ru, it thermodynamically tends to form a stable hcp crystal phase, making the controllable preparation of metastable fcc phase Ru-based metalloalkenes at the two-dimensional scale a significant challenge. Summary of the Invention

[0005] To address the problems of Ru-based hydroxide reaction catalysts in the prior art being prone to oxidation deactivation under high anodic potential conditions, having difficulty in controlling crystal structure, and having insufficient catalytic stability, this invention provides a Pt single-atom-doped fcc-phase RuGa metal ene nanoflower structure and its preparation method.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0007] A Pt single-atom-doped face-centered cubic (fcc) RuGa metalene (Pt SA -RuGa) nanoflower-like structures, including an ultrathin two-dimensional nanoflower-like Ru-based metal alkene framework, wherein Ru is a face-centered cubic crystal phase, Pt is dispersed in the Ru lattice in the form of single atoms, and Ga is distributed in the Ru-based metal alkene as a dopant component, which works with Pt to regulate the crystal structure and electronic structure of Ru.

[0008] Pt single-atom doping can modulate the electronic structure of RuGa metal olefins, optimizing the interaction between Ru active sites and oxygen-containing intermediates. Simultaneously, the introduction of Ga can adjust the electronic properties of Ru active sites, optimizing the adsorption / desorption behavior of hydrogen intermediates. Through the synergistic regulation of Pt single atoms and Ga, the adsorption balance between hydrogen and oxygen-containing intermediates is optimized, thereby improving the catalytic activity and long-term stability of the hydrogen oxidation reaction.

[0009] This invention also provides a method for preparing Pt single-atom-doped fcc-phase RuGa metal ene nanoflower structures. The method comprises the following steps:

[0010] (1) The ruthenium precursor compound, platinum precursor compound and gallium precursor compound were added to a mixed solvent of formaldehyde and water in sequence and mixed evenly. The mixture was then thoroughly mixed under ultrasonic dispersion and stirring conditions to obtain a precursor solution.

[0011] (2) The precursor solution is placed in a closed reaction vessel for a one-step solvothermal reaction. During the reaction, Ru and Ga form a RuGa metal olefin framework, and Pt is doped into the RuGa lattice in the form of single atoms, inducing the RuGa alloy to form an fcc crystal structure. After the reaction is completed, the Pt single-atom doped fcc phase RuGa metal olefin nanoflower structure is obtained by centrifugation, washing and drying.

[0012] Furthermore, in step (1), the ruthenium precursor compound is one or more of ruthenium trichloride, dodecyltriruthenium dodecylcarbonyl, dichloro(p-methylisopropylbenzene)ruthenium(II) dimer, and ruthenium acetylacetonate; the platinum precursor compound is one or more of chloroplatinic acid, platinum acetylacetonate, and sodium tetrachloroplatinate(II); and the gallium precursor compound is one or more of gallium chloride, gallium nitrate hydrate, and gallium acetylacetonate. The ruthenium precursor compound, platinum precursor compound, and gallium precursor compound are thoroughly mixed in the solution to ensure uniform dispersion, so that the Pt source can be dispersed in the Ru lattice in the form of single atoms, optimizing the interaction between the Ru active site and the oxygen-containing intermediate. At the same time, the Ga source is introduced to regulate the electronic properties of the Ru active site and optimize the adsorption / desorption behavior of the hydrogen intermediate.

[0013] Furthermore, the mass ratio of ruthenium precursor compound, platinum precursor compound, and gallium precursor compound in the precursor metal salt is controlled to be 9:1:1 to 17:1:1. Controlling the mass ratio of the ruthenium precursor compound ensures that the catalyst is based on a Ru-based metal olefin, and that Ru transforms from a stable hexagonal close-packed phase to a metastable fcc phase; controlling the mass ratio of the platinum precursor compound ensures that Pt is dispersed in the Ru lattice in single-atom form.

[0014] Furthermore, the mass ratio of platinum precursor compound to gallium precursor compound is controlled at 1:1. When the mass ratio is less than 1:1, Ga occupies too much space, hindering Pt from existing in single-atom form. This prevents the small amount of Pt single atoms from effectively regulating the coordination environment and local electronic structure of Ru atoms. When the mass ratio is greater than 1:1, the overall content is extremely low, and the small amount of Ga cannot fully synergistically regulate Pt single atoms, thus failing to leverage the main role of Pt single atoms. This percentage content allows for the optimization of the adsorption balance of hydrogen and oxygen-containing intermediates through synergistic doping with Pt single atoms to trigger phase transitions without affecting the formation of Pt single atoms, thereby improving the catalytic activity and long-term stability of the hydrogen oxidation reaction.

[0015] Furthermore, in step (2), the solvothermal reaction temperature is 150-170℃, and the solvothermal reaction time is 7-10 h. When the reaction temperature is below 150℃, the reaction temperature not only fails to transform the crystal structure of the precursor solution from hcp to fcc, causing subsequent reactions to be impossible, but also reduces the presence of the Pt source, making it impossible to regulate the electronic structure of the Ru-based metal alkene; when the reaction temperature is above 170℃, the catalyst structure cannot be stabilized, which not only destroys the coordination environment of the Ru-based metal alkene, but also destroys the presence of the Pt and Ga sources. Therefore, this temperature range is selected to effectively synthesize the catalyst, allowing Pt to be doped into the RuGa metal alkene in the form of single atoms, effectively regulating the coordination environment and local electronic structure of the Ru atoms.

[0016] Furthermore, the product was washed sequentially with ethanol and cyclohexane.

[0017] This invention also provides the application of the aforementioned Pt single-atom-doped fcc-phase RuGa metal ene nanoflower structure in the electrocatalytic alkaline hydroxide reaction. SA Using RuGa metal olefin as the working electrode, mercury / mercuric oxide as the reference electrode, and a platinum sheet as the counter electrode, the electrocatalytic hydrogenation performance was tested in a 0.1 M KOH electrolyte. Compared with other catalysts, Pt... SA -RuGa metalenes exhibit a mass activity of 2.8 A·mg at an overpotential of 50 mV. -1 Furthermore, it maintains a stable plateau current density at 1.0 V vs. RHE potential, without significant attenuation.

[0018] Compared to existing technologies, the advantages of this invention are as follows: This invention employs a one-step solvothermal method, using Ru, Pt, and Ga precursors as raw materials. Under solvothermal conditions, it achieves the synergistic doping of Pt single atoms and Ga, realizing the transformation of the Ru phase structure from a stable hexagonal close-packed (hcp) phase to a metastable fcc phase, successfully preparing an fcc phase Ru-based metallene catalytic material with an ultrathin two-dimensional nanoflower morphology. Pt is uniformly dispersed in the Ru lattice in single-atom form and synergistically regulates the crystal and electronic structures of Ru with Ga. The Pt single-atom-doped fcc phase RuGa metallene nanoflower structure is used for electrocatalytic hydrogenation. Through the synergistic regulation of Pt single atoms and Ga, the adsorption balance of oxygen-containing species and hydrogen intermediates is optimized, thereby improving the catalytic activity and long-term stability of the hydrogenation reaction. Electrochemical test results show that the PtSA-RuGa metallene exhibits excellent alkaline hydrogenation reaction activity and good resistance to deactivation under high potential conditions. The preparation process of this invention is simple and reproducible, and it can achieve synergistic regulation of the two-dimensional Ru-based metal olefin crystal phase and electronic structure, providing a new design strategy for the development of high-performance hydrogen fuel cell anode catalyst materials. Attached Figure Description

[0019] Figure 1 The Pt prepared in this invention SA -RuGa metalene (Example 1) (a) and comparative example Pt single-atom doped Ru metalene (Pt SA X-ray diffraction spectra of Ru (Comparative Example 1) (b) and RuGa metalene (Comparative Example 2) (c).

[0020] Figure 2 The Pt prepared in this invention SATransmission electron microscopy (TEM) image (a) of RuGa metalene (Example 1); high-resolution TEM image (b); high-magnification spherical aberration-high-angle annular dark-field scanning TEM image (c); line-scan EDS spectrum acquired along the marked line in image (c), the above figure is a three-dimensional schematic diagram (d).

[0021] Figure 3 The Pt prepared in this invention SA -RuGa metallenene nanoflowers (Example 1) (a) and comparative example Pt SA X-ray photoelectron spectra of Ru metal olefins (Comparative Example 1) (b) and RuGa metal olefins (Comparative Example 2) (c).

[0022] Figure 4 The Pt prepared in this invention SA -RuGa metalene (Example 1), Pt SA -Ru metal alkene (Comparative Example 1), RuGa metal alkene (Comparative Example 2), and electrochemical oxidation polarization curves of commercial Ru / C (a) and comparison of mass activity and specific activity (b).

[0023] Figure 5 The Pt prepared in this invention SA -RuGa metalene (Example 1), Pt SA -Ru metal olefins (Comparative Example 1), RuGa metal olefins (Comparative Example 2), and long-range stability test curves of commercial Ru / C under alkaline conditions for hydrogenation reaction (a); Pt SA Linear scanning voltammetric curve of -RuGa metalene after 10,000 cyclic voltammetric scans (b). Detailed Implementation

[0024] The technical solutions of the present invention will be further described below with reference to the embodiments. These embodiments should not be construed as limiting the technical solutions.

[0025] In the following embodiments, a multi-component synergistically regulated Pt single-atom-doped fcc-phase RuGa metallene nanoflower structure was synthesized in a one-step method and used for electrocatalytic hydrogenation reaction. During the synthesis, an ultrathin two-dimensional nanoflower-like Ru-based metallene framework was successfully synthesized, in which Ru has a face-centered cubic structure, Pt is dispersed in the Ru lattice as single atoms, and Ga is distributed as a dopant component within the Ru metallene, synergistically regulating the crystal and electronic structures of Ru with Pt. Pt single-atom doping can regulate the electronic structure of RuGa-based metallene, optimizing the interaction between Ru active sites and oxygen-containing intermediates; simultaneously, the introduction of Ga can adjust the electronic properties of Ru active sites, optimizing the adsorption / desorption behavior of hydrogen intermediates. Through the synergistic regulation of Pt single atoms and Ga, the adsorption balance between oxygen-containing species and hydrogen intermediates is optimized, thereby improving the catalytic activity and long-term stability of the hydrogenation reaction.

[0026] All reagents used in the following examples are commercially available.

[0027] Example 1

[0028] The synthesis method of Pt single-atom doped fcc phase RuGa metal olefin nanoflowers is as follows:

[0029] (1) 200 mg of ruthenium trichloride, 20 mg of chloroplatinic acid and 20 mg of gallium chloride were dissolved and dispersed in a mixed solvent of 8 mL of formaldehyde and 2 mL of water. After stirring at room temperature for 30 min, the mixture was placed in an ultrasonic machine and sonicated for 15 min to ensure complete dissolution.

[0030] (2) Then the mixed solution obtained in step (1) is transferred to a stainless steel high-pressure reactor with a 20 mL polytetrafluoroethylene liner. The reactor is treated at 160 °C for 8 h to carry out the complete reaction and obtain Pt single-atom doped fcc phase RuGa metal olefin.

[0031] (3) Take the Pt obtained in step (2) SA After the RuGa metal olefin was cooled to room temperature, the reactor liner was placed in an ultra-high pressure system and sonicated for 30 min. Then, it was washed by centrifugation with a mixed solution of ethanol and cyclohexane. The operation was repeated 3 times to obtain the final sample.

[0032] The Pt prepared using Example 1 of this paper SA Using RuGa metal olefin as the working electrode, mercury / mercuric oxide as the reference electrode, and a platinum sheet as the counter electrode, the electrocatalytic hydrogenation performance was tested in a 0.1 M KOH electrolyte. Compared with other catalysts, Pt... SA -RuGa metalenes exhibit a mass activity of 2.8 A·mg at an overpotential of 50 mV. -1Furthermore, it maintains a stable plateau current density at 1.0 V vs. RHE potential, without significant attenuation.

[0033] Example 2

[0034] The synthesis method of Pt single-atom doped fcc phase RuGa metal olefin nanoflowers in this embodiment is as follows:

[0035] (1) 300 mg of ruthenium trichloride, 20 mg of platinum acetylacetonate and 20 mg of gallium chloride were dissolved and dispersed in a mixed solvent of 10 mL of formaldehyde and 2 mL of water. After stirring at room temperature for 30 min, the mixture was placed in an ultrasonic machine and sonicated for 15 min to ensure complete dissolution.

[0036] (2) Then the mixed solution obtained in step (1) is transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner of 20 mL. The reactor is treated at 150 °C for 8 h to carry out the complete reaction and obtain Pt single-atom doped fcc phase RuGa metal olefin.

[0037] (3) Take the Pt obtained in step (2) SA After the RuGa metal olefin was cooled to room temperature, the reactor liner was placed in an ultra-high pressure system and sonicated for 30 min. Then, it was washed by centrifugation with a mixed solution of ethanol and cyclohexane. The operation was repeated 3 times to obtain the final sample.

[0038] Example 3

[0039] The synthesis method of Pt single-atom doped fcc phase RuGa metal olefin nanoflowers in this embodiment is as follows:

[0040] (1) 120 mg of ruthenium trichloride, 10 mg of chloroplatinic acid and 10 mg of gallium acetylacetonate were dissolved and dispersed in a mixed solvent of 10 mL of formaldehyde and 2 mL of water. After stirring at room temperature for 30 min, the mixture was placed in an ultrasonic machine and sonicated for 15 min to dissolve it completely.

[0041] (2) Then the mixed solution obtained in step (1) is transferred to a stainless steel high-pressure reactor with a 20 mL polytetrafluoroethylene liner. The reactor is treated at 160 °C for 10 h to carry out the complete reaction and obtain Pt single-atom doped fcc phase RuGa metal olefin.

[0042] (3) Take the Pt obtained in step (2) SA After the RuGa metal olefin was cooled to room temperature, the reactor liner was placed in an ultra-high pressure system and sonicated for 30 min. Then, it was washed by centrifugation with a mixed solution of ethanol and cyclohexane. The operation was repeated 3 times to obtain the final sample.

[0043] Example 4

[0044] The synthesis method of Pt single-atom doped fcc phase RuGa metal olefin nanoflowers in this embodiment is as follows:

[0045] (2) 200 mg of ruthenium acetylacetonate, 15 mg of chloroplatinic acid and 15 mg of gallium chloride were dissolved and dispersed in a mixed solvent of 6 mL of formaldehyde and 2 mL of water. After stirring at room temperature for 30 min, the mixture was placed in an ultrasonic machine and sonicated for 15 min to ensure complete dissolution.

[0046] (2) Then the mixed solution obtained in step (1) is transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner of 20 mL. The reactor is treated at 170 °C for 9 h to carry out the complete reaction and obtain Pt single-atom doped fcc phase RuGa metal olefin.

[0047] (3) Take the Pt obtained in step (2) SA After the RuGa metal olefin was cooled to room temperature, the reactor liner was placed in an ultra-high pressure system and sonicated for 30 min. Then, it was washed by centrifugation with a mixed solution of ethanol and cyclohexane. The operation was repeated 3 times to obtain the final sample.

[0048] Comparative Example 1

[0049] Pt SA Synthesis of -Ru metalloalkene: 250 mg of ruthenium trichloride and 10 mg of chloroplatinic acid were dissolved in a mixed solvent of 8 mL formaldehyde and 2 mL water. The mixture was magnetically stirred at room temperature for 30 min to ensure complete dissolution of the precursor. The precursor solution was transferred to a 20 mL polytetrafluoroethylene-lined stainless steel high-pressure reactor and subjected to a solvothermal reaction at 160 °C for 8 h. After the reaction, the mixture was allowed to cool naturally to room temperature, and the reaction solution in the reactor liner was sonicated for 30 min. Subsequently, the product was centrifuged and washed three times with a mixed solution of ethanol and cyclohexane to remove unreacted precursor and residual organic matter. Finally, the product was dried to obtain Pt single-atom-doped Ru metalloalkene.

[0050] Comparative Example 2

[0051] Synthesis of RuGa metalloalkene: 250 mg of ruthenium trichloride and 20 mg of gallium chloride were dissolved in a mixed solvent of 8 mL formaldehyde and 2 mL water. The solution was magnetically stirred at room temperature for 30 min to ensure complete dissolution of the precursors. The precursor solution was transferred to a 20 mL polytetrafluoroethylene-lined stainless steel high-pressure reactor and subjected to a solvothermal reaction at 160 °C for 8 h. After the reaction, the mixture was allowed to cool naturally to room temperature, and the reaction solution in the reactor liner was sonicated for 30 min. Subsequently, the product was centrifuged and washed three times with a mixed solution of ethanol and cyclohexane to remove unreacted precursors and residual organic matter. Finally, the product was dried to obtain RuGa metalloalkene.

[0052] Figure 1 The Pt prepared in this invention SA -RuGa metalene (Example 1) (a) and comparative example Pt SA X-ray diffraction patterns of Ru metallene (Comparative Example 1) (b) and RuGa metallene (Comparative Example 2) (c). The XRD diffraction peaks measured in Example 1 of the synthesized material agree with the peaks on the fcc-Ru standard card, confirming the formation of its face-centered cubic structure. In contrast, as Figure 1 b and Figure 1 As shown in c, Pt SA The diffraction peaks of both Ru-metallic olefins and RuGa-metallic olefins correspond to the standard peaks of the Ru hcp phase, indicating that the introduction of a single Pt atom or Ga element alone is insufficient to induce the Ru crystal phase transformation. The synergistic effect of Pt and Ga is the key factor in the formation of the fcc-RuGa crystal phase. Furthermore, Pt... SA The diffraction peak positions of -Ru metal olefins and RuGa metal olefins are basically consistent, and no obvious Pt crystal phase-related diffraction peaks are observed, indicating that Pt does not form an independent crystal phase structure, but exists in the Ru matrix in a highly dispersed single-atom form.

[0053] Figure 2 These are transmission electron microscopy (TEM) images (a), high-resolution TEM image (b), and high-magnification spherical aberration-high-angle annular dark-field scanning TEM image (c) of the Pt single-atom-doped fcc-phase RuGa metallene nanoflowers prepared in this invention (Example 1). Through TEM characterization, Pt can be clearly seen... SA -RuGa metallenes exhibit a nanoflower-like morphology, as shown in high-resolution transmission electron microscopy images, Pt SA The lattice fringe spacing of -RuGa is approximately 0.23 nm, corresponding to the (111) crystal plane of the fcc phase. To further reveal Pt... SA The distribution of Pt atoms in the RuGa metallene was characterized by high-magnification aberration-corrected high-angle annular dark-field scanning transmission electron microscopy. The images revealed a small number of bright spots significantly brighter than their surrounding atoms, and these bright spots were dispersed and did not exhibit any adjacent aggregation. Since aberration-corrected electron microscopy follows the Z-contrast imaging principle, image brightness is approximately proportional to the atomic number. The atomic number of Pt atoms (Z = 78) is higher than that of Ru (Z = 44) and Ga (Z = 31), therefore Pt atoms appear as brighter atomic sites in the images. Combined with the characteristic of uniformly dispersed bright spots and the absence of continuous bright spots or cluster structures, it can be determined that Pt is dispersed in the RuGa metallene lattice as single atoms.

[0054] Figure 3 The Pt prepared in this invention SA -RuGa metalene (Example 1) (a) and comparative PtSA X-ray photoelectron spectra of Ru metalloalkenes (Comparative Example 1) (b) and RuGa metalloalkenes (Comparative Example 2) (c). From the Ru 3p spectrum ( Figure 3 a) It can be seen that the Ru element in Example 1 and Comparative Examples 1 and 2 mainly exists in the metallic state. (Compared to Pt) SA Compared to RuGa, Pt SA The shift in Ru 3p binding energy in RuGa to lower energies indicates that the introduction of Ga promotes electron transfer to Ru sites, thereby modulating the local electronic structure of Ru. (Based on the Pt 4f spectrum...) Figure 3 b) It can be seen that the Pt element in Example 1 and Comparative Example 1 is mainly in the metallic state. Compared to Pt SA -Ru,Pt SA The Pt 4f binding energy in -RuGa shifts further to lower energies, indicating that the introduction of Ga also affects the electronic environment around Pt. Figure 3 As shown in c, since Ga atoms exposed on the surface readily combine with oxygen species, Ga in Example 1 and Comparative Example 2 mainly exists in the oxidized form. Compared to RuGa, Pt SA The shift of the Ga 2p binding energy in RuGa to higher energies indicates that the introduction of a single Pt atom promotes the electronic interaction between Ga and Ru and Pt, causing electron transfer from Ga to the Ru / Pt site.

[0055] Figure 4 The Pt prepared in this invention SA -RuGa metalene (Example 1), Pt SA Electrochemical oxidation polarization curves and comparisons of mass activity and specific activity for Ru metal olefins (Comparative Example 1), RuGa metal olefins (Comparative Example 2), and commercial Ru / C. Figure 4 From a, we can know that Pt SA -RuGa metal olefin nanoflowers exhibited optimal HOR catalytic performance, demonstrating higher current response and better reaction kinetics under the same test conditions, significantly outperforming Pt. SA -Ru, RuGa metal olefins and commercial Ru / C catalysts. Further activity normalization results showed that ( Figure 4 bc), Pt SA -RuGa metal ene nanoflowers exhibit significantly enhanced mass activity and specific activity, reaching 107.5 times and 60.4 times that of commercial Ru / C catalysts, respectively. This indicates that Pt single-atom doping-induced RuGa crystal phase and electronic structure regulation effectively improves HOR catalytic performance.

[0056] Figure 5 This invention demonstrates the Pt prepared according to the present invention. SA-RuGa metalene (Example 1), Pt SA Results of hydrogenation stability tests on Ru metal olefins (Comparative Example 1), RuGa metal olefins (Comparative Example 2), and commercial Ru / C catalysts under alkaline conditions, including long-term chronocurrent response curves and linear sweep voltammetry curves after accelerated durability testing. Figure 5 From a, we can see that during the 10000s constant potential stability test, Pt SA -RuGa metal olefins exhibited the highest current retention rate, significantly outperforming other comparative catalysts, indicating their ability to effectively maintain active site stability and suppress performance degradation under high potential conditions. Furthermore, as... Figure 5 As shown in b, after 10,000 laps of acceleration cycle testing, Pt SA The polarization curves of the -RuGa metal olefins remained largely consistent with those of the initial state, and the plateau current density did not decrease significantly, indicating that the catalyst has excellent long-term operational stability and resistance to deactivation.

[0057] The foregoing has shown and described the basic principles and main features of the present invention, as well as its advantages. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A Pt single-atom-doped face-centered cubic RuGa metallene nanoflower structure, characterized in that, It includes an ultrathin two-dimensional nanoflower-like Ru-based metal alkene framework, in which Ru is a face-centered cubic crystal phase, Pt is dispersed in the Ru lattice in the form of single atoms, and Ga is distributed in the Ru-based metal alkene as a dopant component, which works with Pt to regulate the crystal structure and electronic structure of Ru.

2. The method for preparing Pt single-atom-doped face-centered cubic RuGa metallene nanoflower-like structures according to claim 1, characterized in that, Includes the following steps: (1) The ruthenium precursor compound, platinum precursor compound and gallium precursor compound were added to a mixed solvent of formaldehyde and water in sequence and mixed evenly to obtain a precursor solution; (2) The precursor solution was placed in a closed reaction vessel for a one-step solvothermal reaction. After the reaction was completed, the solution was centrifuged, washed and dried to obtain the Pt single-atom doped face-centered cubic RuGa metal olefin nanoflower structure.

3. The method for preparing Pt single-atom-doped face-centered cubic RuGa metallene nanoflower-like structures according to claim 2, characterized in that, The ruthenium precursor compound is one or more of ruthenium trichloride, dodecyltriruthenium dodecylcarbonyl, ruthenium(II) dichloro(p-methylisopropylbenzene)dimer and ruthenium acetylacetonate; the platinum precursor compound is one or more of chloroplatinic acid, platinum acetylacetonate and sodium tetrachloroplatinate; and the gallium precursor compound is one or more of gallium chloride, gallium nitrate hydrate and gallium acetylacetonate.

4. The mass ratio of the Pt single-atom doped face-centered cubic ruthenium precursor compound, platinum precursor compound, and gallium precursor compound according to claim 2 is controlled to be 9:1:1-17:1:

1.

5. The method for preparing Pt single-atom-doped face-centered cubic RuGa metallene nanoflower-like structures according to claim 2, characterized in that, The volume ratio of formaldehyde to water in the mixed solvent is 3:1 to 5:

1.

6. The method for preparing Pt single-atom-doped face-centered cubic RuGa metallene nanoflower-like structures according to claim 2, characterized in that, The temperature of the solvothermal reaction in step (2) is 150-170℃ and the reaction time is 7-10 h.

7. The method for preparing Pt single-atom-doped face-centered cubic RuGa metallene nanoflower-like structures according to claim 2, characterized in that, Pt is doped into the RuGa lattice in the form of single atoms, inducing the RuGa alloy to form a face-centered cubic phase crystal structure.

8. The method for preparing Pt single-atom-doped face-centered cubic RuGa metallene nanoflower-like structures according to claim 2, characterized in that, The product was washed sequentially with ethanol and cyclohexane.

9. The application of the Pt single-atom doped face-centered cubic RuGa metal olefin nanoflower structure according to claim 1 in the electrocatalytic alkaline hydroxide reaction.

10. The application according to claim 9, characterized in that, Face-centered cubic RuGa metallene nanoflower-like structure, i.e., Pt SA Using RuGa metalloalkene as the working electrode, mercury / mercuric oxide as the reference electrode, and platinum sheet as the counter electrode, the electrocatalytic hydrogenation performance was tested in 0.1 M KOH electrolyte. SA -RuGa metalenes exhibit a mass activity of 2.8 A·mg at an overpotential of 50 mV. -1 Furthermore, it maintains a stable plateau current density at 1.0 V vs. RHE potential, without significant attenuation.